(untitled) (Research, Society and Development, 2020)
In 1966, the military government created the Brazilian MOBRAL Literacy Movement, which was instituted by Law no. 5,379, of December 15, 1967 and implemented in 1970. In this article we present the results of the research we carried out on the booklet prepared by this program. Through the analysis undertaken, it was possible to verify that the booklet was thought and elaborated within the perspective of functional literacy and the ideological order of reproduction of worldviews that place the subjects involved in the teaching and learning process as reproducers of social reality. The MOBRAL / PAF booklet expresses an organization based on a functionalist and ideological conception of education, with subliminal messages, everything indicates, to establish consensual memories, useful for its purpose: the control of social metabolism, conflicts and stimulating nationalism, aiming guarantee the continuity of the productive field based on the division of labor and of men and women in already established social places. One might say that it was structured with the aim of interweaving rhetoric and lessons, to reinforce the perpetuation of a reality, established ad aeternum.